HSC70 expression is reduced in lymphomonocytes of sporadic ALS patients and contributes to TDP-43 accumulation. Issue 1 (2nd January 2020) - Arosio, Alessandro; Cristofani, Riccardo; Pansarasa, Orietta; Crippa, Valeria; Riva, Chiara; Sirtori, Riccardo; Rodriguez-Menendez, Virginia; Riva, Nilo; Gerardi, Francesca; Lunetta, Christian; Cereda, Cristina; Poletti, Angelo; et al.
Abstract: Aim : The demonstration that chaperone-mediated autophagy (CMA) contributes to the degradation of TDP-43, the main constituent of cytoplasmic inclusions typically found in motor neurons of patients with sporadic amyotrophic lateral sclerosis (sALS), has pointed out a possible involvement of CMA in aggregate formation. To explore this possibility, in this study, we verified the presence of a possible systemic CMA alteration in sALS patients and its effect on TDP-43 expression. Materials and methods : Gene and protein expression of the cytosolic chaperone HSC70 and the lysosome receptor LAMP2A, the two pivotal mediators of CMA, was assessed in peripheral blood mononuclear cells (PBMCs) derived from 30 sALS patients and 30 healthy controls. The expression of TDP-43 and co-chaperones BAG1 and BAG3 was also analyzed. Results : We found reduced HSC70 expression in patient cells, with no change in LAMP2A, and increased insoluble TDP-43 protein levels, with an aberrant intracellular localization. We also observed an unbalanced expression of co-chaperones BAG1 and BAG3. HSC70 down-regulation was confirmed in immortalized lymphoblastoid cell lines derived from sporadic and TARDBP mutant ALS patients. Lastly, we demonstrated that HSC70 silencing directly increases TDP-43 protein levels in human neuroblastoma cells. Discussion : Our results do not support the existence of a systemic CMA alteration in sALS patients but indicate a direct involvement of HSC70 alterations in ALS pathogenesis.